Effects of vibration onto the flow structures and dynamics of gas-liquid two-phase flow / Mohd Zamri Zainon - Mohd Zamri , Zainon (2013)
The investigations on the effects of heavy class disaster shakes and vibration have been conducted for the bubble column and vertical upward gas-liquid two-phase flow channel via experimental studies. The effects of four modes of vibrations with ground accelerations in the range of 0~12 m/s2 were examined using a specially constructed vibration platform that move vertically. The facility was equipped with high speed video camera and sensors for various parameters measurement. The first part of the work focused on the behavior of the rising bubble in a 2-D column of air-water with further analyses on the rising velocity of the gas bubbles at various sizes. The results revealed that the behavior of rising bubble has a totally different characteristic when compared to the situation with the absent of vibration. The coalescences of bubbles with clustering and breakup were seen and for the most critical case, the bubble distorted very badly under the effect of vibration with higher modes. On the other hand, the rising velocity of gas bubbles shows some range fluctuation compared to normal rise without vibration. The bubbles move very quickly during the positive acceleration and show slower movement during the negative acceleration. The second part of this work concentrated on the flow patterns, flow patterns mapping, measurement of void fraction and instantaneous bubble velocity under the same range of ground acceleration with various flow condition. Under the vibration effects, the flow pattern change very easily for example from bubbly to slug flow during the low liquid superficial velocities and they show very obvious patterns transition as the gas superficial velocities increased. At higher liquid superficial velocities, as a result of higher dynamic force from the liquid flow, the change of flow patterns was not so critical but at some level the transition of patterns can be observed particularly for higher gas superficial velocities. From the flow pattern analysis, the data were then interpreted into the flow mapping where completely different maps were constructed based on the sizes of vibrations and flow conditions. On the other hand, the measurements of void fraction were performed using the Constant Electric Current Method sensor that is capable to measure both the void fraction and the liquid film thickness, and therefore the effect of annular flow on the measurement can be avoided. The results show that as the liquid superficial velocity increases the fluctuation of void fraction receives very small effect from the vibration. In addition the effects of axial location were also conducted in order to investigate the variation of void fraction along the flow channel. The numerical data from void fraction measurement were then used to calculate the instantaneous bubble velocity. Using the peaks of voids from the graph and the relation of distance and time travels of the bubbles and slugs contribute to calculations of their velocities. During these calculations, the void peaks were compared with the sinuous motions during the vibration and as a result the effects of negative and positive acceleration on the bubbles velocities were analyzed. In this case, the bubble velocities were strongly affected by the scale of vibrations but they differ in term of speed during the positive and negative acceleration. However, for the case of high velocity liquid flow regime, the influences of vibration were seen to be very low. In general, throughout this thesis work, the effects of vibration onto the flow structures and dynamics of gas-liquid two-phase flow are very obvious. The results can be a good reference for the safety design and analysis on the two-phase flow, particularly on the problems regarding heavy disaster shakes as discussed in this thesis.